Aerosmith: masterpiece (Veo Star, 2006)
El DVD contiene los siguientes temas Eat The Rich, Toys In The Attic, Fever, Draw The Line, Rag Doll, Cryin, Crazy, Monkey On My Back, Mama King, Shut Up And Dance,Stop Messin 'Round, Walk On Down, Janie's Got A Gun, Love In An Elevator, Dude (Looks Like A Lady), Sweet Emotion, Come Together, Dream On, Living On The Edge, Walk This Way.